The development of regional smart energy systems in the World and China: The concepts, practices, and a new perspective. (26th April 2021) - Zhao, Yunlong; Ma, Linwei; Li, Zheng; Ni, Weidou
Abstract: To realize a low‐carbon and sustainable energy transition, smart energy systems (SES) assisted by data and information technology are regarded as promising solutions for energy system integration (ESI) and have been put into regional practices. However, there is still lacking attention on the development of multiregional smart energy systems (MRSES), which include three or more areas. This article aims to analyze concepts and practices of SES and enlighten a new perspective of MRSES. The conceptual evolution and regional practices of SES in the world were first reviewed, and it was found out that SES does not means the end of the conceptual evolution of ESI. Current regional practices are still limited in small areas, being typically remote areas, urban areas, and industrial areas. Secondly, the review of concepts and practices of SES in China indicate that the understanding of SES concepts are still confusing in national scale, and the apparent regional disparity in China is calling attention on the development of MRSES. Finally, a preliminary concept of MRSES was proposed and its perspective in China and the world, which is composed by four connected sub‐SES and named as a coordinated development of "smart energy farms + smart energy towns + smart energy industrial parks + smart energy transportation networks" was discussed. The former three sub‐SES are identified according to various economic characteristics and resources endowment in different regions, and they are all connected by the forth sub‐SES. Although this concept is still preliminary, it provides an imagination of future large‐scale SES, and the realization of this concept needs further breakthrough of data technology. This article is categorized under: Application Areas > Industry Specific Applications Application Areas > Government and Public Sector Application Areas > Society and Culture Abstract : A preliminary concept of multiregional smart energy systems